Magnetic Resonance Imaging of Rheumatoid Arthritis: Peripheral Joints and Spine - Reijnierse, Monique; Helm-Mil, Annette van der; Eshed, Iris; Schueller-Weidekamm, Claudia (Seminars in Musculoskeletal Radiology, 2018)
Both the fields of rheumatology and radiology are changing rapidly. Effective medication has become available for rheumatoid arthritis (RA) and transformed it from a progressive disabling disease into a chronic disease. Indications for magnetic resonance imaging (MRI) have changed accordingly, shifting toward early detection. There is also an overall increased clinical demand for high-end imaging. Together with improvement of MRI units and sequences, MRI protocols are adapted based on clinical indications. This article addresses (1) the clinical background and present role of MRI in early disease detection, (2) RA involvement of peripheral joints, (3) RA involvement of the spine, and (4) state-of-the-art RA MRI protocols. The key toward cost-effective MRI examination in RA is communication between radiologist and rheumatologist as well as awareness and knowledge of the basics and advancements in both fields.
Keywords: rheumatoid arthritis; magnetic resonance imaging; joints; spine; inflammation